O objeto não fala por si só: o papel da mediação documentária nos acervos musealizados - Janine Menezes Y Ojeda (2016)
Based on the concept of musealization, the dissertation aims to address reflections on the term "mediation", focusing directed in the documentary framework, implicit in the contemporary museum panorama. In predecessor character it is developed a dialogue withthe document of concepts and museums of the belgian Paul Otlet (1868-1944), commonly known as "Father of documentation." The study is focused on the information organization, which is characterized as a vital procedure for the production and circulation of documentarycontent. Over the sections, the approach involves aspects directly linked to musealized object, focused on the influence of mediation and resizing the documentary space compared to the production of knowledge generated from the museological heritage. Once integrated into the notional field of Museology by different authors, the concepts of musealization, museality and mediation are configured as research foundations, in order to position the concepts of document and documentation in museums and enhance the communication ofthe contents produced from the museum collections. In this respect, it is considered the contribution of contemporary conceptions, especially from the french line, with regard to documentaries mediation and space, which lead to the reflection on new forms of connection made by museum professionals in compliance with the use of demands of information,making the user an active agent in the construction of his own knowledge.